Molecular Characterization of Mesoporous Silica (Un)loading by Gemcitabine and Ibuprofen – An Interplay of Salt-Bridges and Hydrogen Bonds - Aziz, Awin; Macht, Moritz; Becit, Bahanur; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2024)
The molecular mechanisms of mesoporous silica nanomaterial (MSN) loading by gemcitabine and ibuprofen molecules, respectively, are elucidated as functions of pore geometry. Based on a small series of MSN archetypes, we use molecular dynamics simulations to systematically explore molecule-by-molecule loading of the carrier material. Apart from predicting the maximum active pharmaceutical ingredient (API) loading capacity, more detailed statistical analysis of the incorporation energy reveals dedicated profiles stemming from the interplay of guest-MSN salt-bridges/hydrogen bonding in concave and convex domains of the silica surfaces - which outcompete interactions among the drug molecules. Only after full coverage of the silica surface, we find secondary layer growth stabilized by guest-guest interactions exclusively. Based on molecular models, we thus outline a two-step type profile for drug release from MSN networks. Subject to the MSN structure, we find 50–75 % of the API within amorphous domains in the inner regions of the pores – from which drug release is provided at constant dissociation energy. In turn, the remaining 50–25 % of drug molecules are drastically hindered from dissociation.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Drug release; Mesoporous silica; Solubility

Molecular Simulation Analyses of Polymorphism Control Factors by the Example of Carbamazepine Forms I-IV: A Blueprint for Industrial Drug Formulation? - Gadelmeier, Andreas; Macht, Moritz; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2022)
We outline comparably simple molecular simulation techniques to elucidate the interactions that determine the polymorphism of carbamazepine. Starting from the established GAFF molecular mechanics model, only a small series of tailor-made improvements is needed to tackle the subtle differences in the interaction energies of polymorphs I - IV. On this basis, molecular dynamics simulations provide melting enthalpies at < 1 kcal/mol accuracy (0.2 kcal/mol for forms I-III) as compared to the experiment. Yet, the predicted stability ranking of III > I > II > IV only partially reproduces the experimentally observed III > I > IV > II series. Despite this limitation, we demonstrate how insights from molecular simulation offer the elucidation of possible factors for polymorph control. Apart from characterizing bulk crystals, we outline the evaluation of size-dependent profiles of crystallite formation energy. Contrasting the contributions of bulk, surface and edge terms to the formation energy of nano-scale precipitates, we suggest a multi-step nucleation mechanism leading from amorphous aggregates to crystallites. We argue that carbamazepine aggregates of less than ∼100 molecules adopt a spherical shape to minimize edge/surface energy – overcompensating the loss in bulk energy inherent to non-crystalline ordering in the inner core. In turn, for large crystallites polymorph form III is preferred, whilst suitable spatial confinement to crystallites of 100–500 carbamazepine molecules appears to promote form II.
CRIS-Team Scopus Importer:2022-07-22
Keywords: Crystal engineering; Drug formulation; Molecular simulation; Polymorphism

MRGPRX2 ligandome: Molecular simulations reveal three categories of ligand-receptor interactions - Maier, Philip; Macht, Moritz; Beck, Silvan; Kolkhir, Pavel; Babina, Magda; Kremer, Andreas; Zahn, Dirk; Wolf, Katharina (Journal of Structural Biology, 2025)
Introduction: Mas-related G protein-coupled receptor (MRGPR) X2 is a mast cell receptor known to be activated by a wide range of ligands of various size, charge and origin. Our aim is to gain a deeper understanding of the binding processes of the different MRGPRX2 ligands and the ligand-receptor interactions in order to identify crucial structural elements for receptor activation. Materials and methods: We used the three-dimensional structure of MRGPRX2 described in Nature in 2021 by Cao et al. and Yang et al. to computationally model the interaction between MRGPRX2 and small molecule ligands under simulated physiological conditions. Results: Docking and post-docking samplings of the MRGPRX2 ligandome within the GPCR binding pocket led to the identification of key structural features for protein–ligand interactions. On the ligand side, we obtained an overlay of different molecular patterns or chemical groups by comparing different ligands plotted on the receptor. These key features include at least one protonated amine moiety of MRGPRX2 ligands contributing to one salt-bridge and one π-cation interaction, as well as an extended non-polar domain of the ligand surface that offer hydrophobic segregation and/or π-stacking interactions. In the receptor, we identified amino acids (GLU164, ASP184, PHE101, PHE170, TRP243, PHE244 and PHE257) that specifically interact via hydrogen bonding, salt-bridges, π-cation interactions and π-π stacking with the ligands to direct binding and ultimately receptor activation. Discussion: Our insights into ligand-receptor interaction obtained by molecular modeling can help to predict mast cell activation via MRGPRX2 including adverse reactions, and facilitate the development of MRGPRX2 antagonists for the treatment of mast cell-mediated diseases.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Docking; Ligand-receptor interaction; Mas-related G protein coupled receptor X2; Molecular recognition; Pharmacophore

On the pK of crystal surfaces: molecular modeling of crystallite protonation, local reorganization, and solute dissociation - Duchstein, Patrick; Macht, Moritz; Zahn, Dirk (CrystEngComm, 2025)
We demonstrate the application of the ‘instantaneous pK’ approach to the molecular dynamics simulation of crystallite models exposed to an acidic solvent environment. For this, the bulk solution properties pH and pK are scrutinized into local aspects and effectively characterized for individual molecules of crystal faces, edges and steps, respectively. To illustrate this concept, we introduce two prototype cases: the acid-induced dissociation of i) calcite and ii) carbamazepine (CBZ, form III) drugs. We find acid-induced calcite dissociation follows a rather intuitive mechanism, namely the protonation of crystal edges/steps leading to ion-by-ion dissociation of HCO3− and Ca2+ species into water. In contrast, our simulations of CBZ solvation at pH = 3 and pH = 2, respectively, reveal a more complex dissolution behavior. The molecular crystals were found to accommodate a substantial degree of CBZ protonation without drug release to the solvent. Instead, the crystallite edges and corners are re-arranged in favor of a surprisingly stable core-shell structure featuring a CBZ core and a mixed CBZ/CBZH shell of +0.005 and +0.03 C m−2 surface charge at pH = 3 and pH = 2, respectively. The resulting crystallite models are persistent and even more drastic acidity is needed to enable actual dissociation of CBZH into water.
CRIS-Team Scopus Importer:2025-03-14

On the Role of Silica Carrier Curvature for the Unloading of Small Drug Molecules: A Molecular Dynamics Simulation Study - Macht, Moritz; Becit, Bahanur; Zahn, Dirk (Journal of Pharmaceutical Sciences, 2020)
We present atomic scale models of differently shaped silica surfaces loaded by gemcitabine and ibuprofene molecules. Despite the dissimilar nature of the drug molecules, their association to silica carriers shows quite similar characteristics. We identify a well-defined contact layer that is stabilized by silica-molecule salt-bridges/hydrogen bonding in parallel to interactions among the drug molecules. Additional loading of the carriers leads to rough films with dynamically evolving asperities rather than layer-by-layer ordering. To elucidate the role of differently shaped silica surfaces, we compared planar slab models and spherical nanoparticles as 2 limiting cases. Despite the strong difference in the curvature of the silica surfaces, our molecular dynamics simulations show only small changes of the unloading characteristics. This suggests that the design of different pore shapes in mesoporous silica–based drug carriers mainly affects the migration kinetics rather than the energetics of drug loading and release.
CRIS-Team Scopus Importer:2020-04-14
Keywords: drug delivery system(s); drug transport; molecular dynamics; molecular modeling; nanoparticle(s)

Organic Nucleation: Water Rearrangement Reveals the Pathway of Ibuprofen - Lu, Hao; Macht, Moritz; Rosenberg, Rose; Wiedenbeck, Eduard; Lukas, Max; Qi, Daizong; Maltseva, Daria; Zahn, Dirk; Cölfen, Helmut; Bonn, Mischa (Small, 2024)
The organic nucleation of the pharmaceutical ibuprofen is investigated, as triggered by the protonation of ibuprofen sodium salt at elevated pH. The growth and aggregation of nanoscale solution species by Analytical Ultracentrifugation and Molecular Dynamics (MD) simulations is tracked. Both approaches reveal solvated molecules, oligomers, and prenucleation clusters, their size as well as their hydration at different reaction stages. By combining surface-specific vibrational spectroscopy and MD simulations, water interacting with ibuprofen at the air–water interface during nucleation is probed. The results show the structure of water changes upon ibuprofen protonation in response to the charge neutralization. Remarkably, the water structure continues to evolve despite the saturation of protonated ibuprofen at the hydrophobic interface. This further water rearrangement is associated with the formation of larger aggregates of ibuprofen molecules at a late prenucleation stage. The nucleation of ibuprofen involves ibuprofen protonation and their hydrophobic assembly. The results highlight that these processes are accompanied by substantial water reorganization. The critical role of water is possibly relevant for organic nucleation in aqueous environments in general.
CRIS-Team Scopus Importer:2024-02-02
Keywords: nonclassical nucleation; organic nucleation; prenucleation cluster; sum frequency generation spectroscopy; water at interface

Supraparticles for Bare-Eye H2 Indication and Monitoring: Design, Working Principle, and Molecular Mobility - Reichstein, Jakob; Schötz, Simon; Macht, Moritz; Maisel, Sven; Stockinger, Nina; Cuadrado Collados, Carlos; Schubert, Katrin; Blaumeiser, Dominik; Wintzheimer, Susanne; Görling, Andreas; Thommes, Matthias; Zahn, Dirk; et al. (Advanced Functional Materials, 2022)
Indicators for H2 are crucial to ensure safety standards in a green hydrogen economy. Herein, the authors report micron-scaled indicator supraparticles for real-time monitoring and irreversible recording of H2 gas via a rapid eye-readable two-step color change. They are produced via spray-drying SiO2 nanoparticles, AuPd nanoparticles, and indicator-dye resazurin. The resulting gas-accessible mesoporous supraparticle framework absorbs water from humid atmospheres to create a three-phase-system. In the presence of H2, the color of the supraparticle switches first irreversibly from purple to pink and further reversibly to a colorless state. In situ infrared spectroscopy measurements indicate that this color change originates from the (ir)reversible H2-induced reduction of resazurin to resorufin and hydroresorufin. Further infrared spectroscopic measurements and molecular dynamics simulations elucidate that key to achieve this functionality is an established three-phase-system within the supraparticles, granting molecular mobility of resazurin. Water acts as transport medium to carry resazurin molecules towards the catalytically active AuPd nanoparticles. The advantages of the supraparticles are their small dimensions, affordable and scalable production, fast response times, straightforward bare-eye detection, and the possibility of simultaneously monitoring H2 exposure in real-time and ex post. Therefore, H2 indicator supraparticles are an attractive safety additive for leakage detection and localization in a H2 economy.<br
Keywords: hydrogen indicators; hydrogen sensors; in situ DRIFTS measurements; MD simulations; smart additives; supraparticles